PEMANFAATAN MEDIA SKETCHUP UNTUK MENINGKATKAN KETERAMPILAN DESAIN SISWA SMK - Alfandi Ziqri (CV. ADIBA AISHA AMIRA, 2024)
The advancement of digital technology has revolutionized various fields, including education. SketchUp, a user-friendly 3D design software, has become a popular learning medium in the digital era. This study aims to examine the effectiveness of using SketchUp media to improve the design skills of SMK students through a literature review method. The method used is a literature review by examining various information sources such as scientific journals, scientific articles, and research reports. SketchUp helps students better visualize their design ideas, understand design concepts more easily, and improve their ability to solve design problems. Training is needed for teachers to improve their ability to use SketchUp in teaching.